Synthesis of sulfonated bio-based catalysts for the esterification of palm fatty acid distillate - Akinfalabi, Shehu-Ibrahim (2019)
The synthesis of sulfonated of bio-based catalysts from palm seed cake (PSC), sugarcane bagasse (SCB) and kenaf seed cake (KSC), for the esterification of palm fatty acid distillate (PFAD), have been demonstrated in this work. The derived biomass materials were subjected to different levels of pretreatment that is triggered by the chemical activation period over ortho-phosphoric acid. The pretreated biobased materials were calcined at different temperatures in a nitrogen controlled atmosphere for about 2 to 5 h at 400 OC. The average SULFONATION time and temperature were between 5 to 12 h and 230 ᵒC. Whereas, the volume of the sulfonating agents used were between 100 – 250 mL in concentrated form.